Oil of C. sinensis inhibits pathogenic bacteria - Folorunso Olufemi Samuel; Adeola Segun A; Marycelin Mandu Baba; Jill Farrant (International Journal of Phytomedicine, 2013)
Context: In spite of great advances observed in modern medicine, plants still make an important contribution to health care. Hence, there is need for unrelenting effort in the exploration of the health benefit of medicinal plants. Purpose: This work was designed to determine the role of the volatile oil of Camellia sinensis on the extracellular protease, which is one of the major virulent factors in the pathogenesis of Shigella dysenteriae and its antibacterial effects on eight other enteric bacterial as compared with the antibiotics Finding: The total antimicrobial effect of the volatile oil (355.0 mm) was significantly higher (p<0.05) than the antibiotics tested (203.0 mm). The minimum inhibitory and bactericidal concentrations of the oils revealed Escherichia coli as the most sensitive. However, relatively higher concentrations of the oils is required to achieve similar sensitivity against Salmonella and Shigella species. The activity of the partially purified extracellular protease, which is one of the virulence factors of Shigella dysenteriae was inhibited by the oil from different parts of the plant especially the leaf. The activity of this enzyme increased steadily between pH 7.0 – 8.0 and 40 – 50 oC. Summary: The volatile oils possessed antimicrobial activity and showed both competitive and noncompetitive kinetic inhibition of the extracellular protease of Shigella dysenteriae. Implication: The inhibitory action of the oil on protease from Shigella dysenteriae suggests the possible mode of action. Volatile oil from Camellia sinensis, especially the leaf, may be an important source of antibiotic against these organisms particularly Shigella dysenteriae.